2004
DOI: 10.2174/0929867043364766
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance and Anticonvulsants: New Studies with Some Enaminones

Abstract: The multidrug resistance (MDR), often conferred by the active extrusion of drugs from the cell, is a phenomenon often seen in cancer cells that may become resistant to a wide spectrum of drugs with varying chemical structures or cellular targets. This event has recently been reported for anticonvulsants. Studies in our laboratories on this occurrence with some enaminones have shown that the enaminones display high efflux ratios and are recognized by P-glycoprotein (P-gp) and/or the multidrug resistance protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 72 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…The anticonvulsants phenytoin and carbamazepine prolong the inactive state of the VGSCs, and more recently, lamotrigine, zonisamide, and rufinamide have appeared and their modes of action suggest an involvement of sodium channel blockade 33. In our studies on the anticonvulsant activity of the enaminones6, 7, 14, 34–44 we found that they act as inhibitors of the VGSCs 31, 38. In our work on analogues of the classic pharmacophore, 35 , it was noted that anticonvulsant activity was maintained when R = H, CH 3 , C 2 H 5 , or C(CH 3 ) 3 and when X = + σ 35.…”
Section: Synthetic Studies and Qsar Analysis Of The Enaminonesmentioning
confidence: 61%
See 1 more Smart Citation
“…The anticonvulsants phenytoin and carbamazepine prolong the inactive state of the VGSCs, and more recently, lamotrigine, zonisamide, and rufinamide have appeared and their modes of action suggest an involvement of sodium channel blockade 33. In our studies on the anticonvulsant activity of the enaminones6, 7, 14, 34–44 we found that they act as inhibitors of the VGSCs 31, 38. In our work on analogues of the classic pharmacophore, 35 , it was noted that anticonvulsant activity was maintained when R = H, CH 3 , C 2 H 5 , or C(CH 3 ) 3 and when X = + σ 35.…”
Section: Synthetic Studies and Qsar Analysis Of The Enaminonesmentioning
confidence: 61%
“…We have provided an abbreviated summary of the field of enaminone synthesis, and evaluation of the active analogues and evolving mechanism(s) of anticonvulsant activity. The fact that this is the fourth in a series (previous summaries see Refs 6, 7, 42…”
Section: Discussionmentioning
confidence: 85%
“…In a previous study, Seelig and coworkers suggested that substrate recognition patterns for human P-gp consists of two electron donor groups with a spatial separation of 2.5 AE 0.3 Å (type I units) or three electron donor groups with a spatial separation of the two outer groups of 4.6 AE 0.6 Å (type II units) [23]. Based on this theory, DM27 is in excellent agreement with the bond lengths and lipophilicity with A:}B: (vinyl hydrogen on C 2 }N-H hydrogen) of 2.573 Å and A:}C: (vinyl hydrogen on C 2 }Carbonyl oxygen) of 5.691 Å [24]. In this study, Caco-2 cells were incubated with DM27 (10 À10 -10 À4 M) and the transport of antiviral agents, paracellular and transcellular markers was conducted.…”
Section: Discussionmentioning
confidence: 88%
“…Enaminones are enamines of β-dicarbonyl compounds, whose chemistry and activities in models of diseases or disorders, principally seizures, have been reviewed before 1 2 3 . Enamines are unstable in aqueous solutions whereas, enaminones are chemically stable.…”
mentioning
confidence: 99%
“…Enaminones are formed by a reaction between a primary amine and a β-dicarbonyl compound. They have been used as intermediates or building blocks in synthetic and medicinal chemistry 1 2 3 but they also have biological activities. One of the early studies published as an abstract reported analgesic, papaverine-like, and anticonvulsant activities of an enaminone compound 4 .…”
mentioning
confidence: 99%